The Effect of Co-Metabolism on Removal of Hexadecane by Microbial Consortium from Soil in a Slurry Sequencing Batch Reactor - majid nozari; Mohammad Reza Samaei; Mansooreh Dehghani (Shiraz University of Medical Sciences, 2014)
Background: Among Alkanes, N-Alkanes with medium chain have been identified as the most important contaminants of the soil. N-hexadecane (C16H34) with low solubility in water also belongs to this group and has been used by many researchers as a model contaminant. The present study aimed to investigate the effect of the external source of carbon (glucose) as co-substrate on removal of hexadecane from the soil.Methods: In this study, a Slurry Sequencing Batch Reactor (SSBR) was used as a pilot by a bacterial consortium, including bacterium Acinetobacter radioresistens, Bacillus subtilis, and Pseudomonas aeruginosa, in order to remove different concentrations of hexadecane (1,4,7, and 10 percent).Sampling was performed four times during the sedimentation step. Then, the samples were analyzed by GC-FID and the results were analyzed statistically.Results: The results showed that hexadecane removal (%) by the microbial consortium was higher in lower initial concentrations in such a way that the biological removal of hexadecane was respectively 45.95%, 38.55%, 34.39%, and 32.40% in the concentrations of 1%, 4%, 7%, and 10% on the third day. Moreover, adding the external carbon source (glucose) on the first day caused a 16% increase in hexadecane removal, which is 1.4 times more than the amount of hexadecane removal in the conditions without co-metabolism.Conclusion: The results showed that SSBR could be used as an exit-situation effective method for hexadecane removal in low concentrations through considering the effective factors in its function, such as dissolved oxygen, pH, and temperature. Also, adding the secondary carbon source could be effective in hexadecane removal from the soil. Yet, this effect might vary on different days.